On the sulutions of a fractional differemtial equation - Cui, Runqing (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
We have showed the results obtained in [1] are incorrect and the fractional complex transform is invalid to the fractional differential equation which contain modified Riemann-Liouville fractional derivative.